Positivity of repeat nasal MRSA PCR screening: a single-center experience - Ali Earl; Sage Greenlee; Karen Fong; Hannah Imlay; Emily S. Spivak (Cambridge University Press, 2023)
Repeating nasal methicillin-resistant Staphylococcus aureus (MRSA) polymerase chain reactions (PCRs) within 14 days may increase healthcare costs and inform anti-MRSA antibiotic therapy without known benefit. Within an inpatient admission, our retrospective, single-center evaluation found that conversion from negative to positive on repeat nasal MRSA PCR screen was uncommon (2%).